Impact of the Fluoroquinolones on Gastrointestinal Flora - KORTEN, VOLKAN (My University, 1993)
A number of studies have been performed to evaluate the effect of the fluoroquinolones on gastrointestinal flora. The fluoroquinolones have only slight or no effect on the oropharyngeal flora, except when Neisseria, Haemophilus or Branhamella spp. are present. Studies have consistently shown that Gram-negative facultative bacteria of the lower intestinal flora are strongly suppressed during administration of these agents. Total faecal anaerobes are generally unchanged. The effect of the fluoroquinolones on Gram-positive bacteria is more variable with mild to moderate suppression reported with some agents. In view of the high faecal concentrations of the fluoroquinolones, the general lack of effect on anaerobes is surprising; it may be attributable to the large number of microorganisms found in faeces and faecal binding of the fluoroquinolones. Several recent studies suggest that the effects of some fluoroquinolones on faecal anaerobes and Gram-positive cocci may be more profound in certain patient populations such as bone marrow transplant recipients and patients undergoing gastrointestinal surgery. Colonisation with yeasts and the emergence of resistant bacterial strains have been reported during or after fluoroquinolone administration in some studies. Future studies will need to investigate the effect of the newer agents with greater activity against anaerobes and Gram-positive cocci on the gastrointestinal flora and to continue surveillance for resistant organisms. © 1993, ADIS International Limited. All rights reserved.